PHENOLOGY OF PISTACHIO TREES IN OLTIARIQ DISTRICT OF FERGANA REGION (REPUBLIC OF UZBEKISTAN) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Studying phenological processes allows future management of the utilization potential of this species. In addition, understanding phenological patterns increases the ability to use plants for various purposes and to influence quality indicators. As a result, productivity and quality parameters can be improved. Phenological observations of pistachio trees in Oltiariq District of Fergana Region may contribute to enhancing pistachio productivity and nut quality in this area in the future.
Keywords: pistachio, nut crop, breeder, irrigated land, agriculture, mountains and foothills, forest, farm enterprise, phenology